(3hGbY JOQjS GdJGQjN hJbjje fJGFLg aj GdeOGQS GdQSejI GddHfGfjI (B((3GdUa GdJGSY GdCSGSj(B)s - (3GdRjf, fOi jhSas ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2002)
(3Ef GdJGQjN ceGOI eOQSjI JhGLg aj dHfGf eTcdGJ cKjQI eeG jLYdgG eGOI OSeI ddHMK(B. (3ef gfG JgOa gPg GdOQGSI Edi JfGhd eGOI GdJGQjN ef MjK efGgL GdJOQjS, GdcJGH GdeOQSj, eDgdGJ eYdej GdJGQjN hCfXeI GdGeJMGfGJ hGdJbjje hPdc aj GdeOGQS GdQSejI GdJj JTQa YdjgG hRGQI GdJQHjI GdhWfjI hGdafhf GdLejdI, haj GdUa GdJGSY CSGSj JMOjOG(B. (3EJHYJ GdOQGSI GdefgL GdJMdjdj MjK Je JMdjd efGgL GdJGQjN aj dHfGf efP YgO GdGfJOGH hGdCSFdI hWQb GdJUMjM aj GdGeJMGfGJ GdQSejI cPdc JMdjd GdGQGA GdTNUjI GdJj jHOjgG GdJdGejP hGdeYdehf ef NdGd GSJHjGf hRY Ydjge Mhd eSCdI GdJbjje(B. (3NdUJ GdOQGSI Edi Cf WQGFb JOQjS eGOI GdJGQjN JbdjOjI eeG jfYcS SdHG Ydi Jbjje fJGFLg(B. (3CeG HGdfSHI deYdej GdJGQjN age jYGfhf fbUG aj GdJOQjH Ydi JOQjS GdJGQjN hGdEYOGO Ydi hSGFd GdJbjje GdMOjKI(B. (3CeG Yf WQGFb Jbjje eGOI GdJGQjN agj GNJHGQGJ ef fhY CSFdI GdebGd GdJj JYJeO Ydi GdPGcQI hgj eQJHWI HbjGS OQLI MaX GdJdejP ddeYdheGJ(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Public Sector Intermediate Education History Education School Evaluation; Secteur Public Cycle moyen Enseignement de l'histoire Evaluation Scolaire; (3GdJYdje GdQSej GdeQMdI GdeJhSWI JYdje GdJGQjN GdJbjje GdeOQSjs